Gut microbiome dysbiosis implicates the gut-bone axis in Modic changes: a metagenomic case–control study - Lan, Binbin; Liang, Yu; Zhou, Zhongxian; Liu, Jianwei (Frontiers in Microbiology, 2025)
IntroductionModic changes (MCs) are vertebral endplate lesions strongly associated with discogenic low back pain (LBP), though their pathogenesis remains poorly understood. Emerging evidence implicates gut microbial dysbiosis in systemic inflammation and musculoskeletal disorders, yet its potential role in MCs has not been investigated. This study aimed to characterize the gut microbiome in patients with MCs and identify microbial and metabolic features linked to disease severity.MethodsIn a case–control study, shotgun metagenomic sequencing was performed on fecal samples from 31 patients with MCs (16 Type 1, 15 Type 2) and 25 age- and sex-matched healthy controls. Microbial community structure was assessed via alpha and beta diversity analyses. Differential taxa and predictive biomarkers were identified using linear discriminant analysis effect size (LEfSe) and Random Forest modeling. Functional potential was evaluated via Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Associations between microbial features and clinical markers (C-reactive protein [CRP], Pfirrmann grade) were also examined.ResultsPatients with MCs showed significantly reduced gut microbial alpha diversity compared to controls (Chao1 index: p = 0.005; Shannon index: p = 0.034; Simpson index: p = 0.042), with the most pronounced reduction in Type 1 MCs. Beta diversity analysis revealed distinct microbial communities between groups (PERMANOVA, p = 0.001). Key discriminative taxa included unclassified_Parabacteroides (AUC = 0.895) and Bacteroides uniformis (AUC = 0.889). Metabolic pathway analysis identified 52 differentially abundant pathways, with significant enrichment of quorum sensing (p < 0.001) and glycerolipid metabolism (p < 0.001) in MC patients, both strongly correlated with elevated CRP and higher Pfirrmann grade (p < 0.001).DiscussionGut microbial dysbiosis is associated with MCs, marked by reduced diversity, specific bacterial biomarkers, and altered metabolic pathways related to inflammation and tissue degeneration. These results suggest a potential role of the gut–bone axis in MC pathogenesis and highlight novel targets for diagnostic and therapeutic strategies in LBP.